Pengaruh Penggunaan Media Video Youtube Terhadap Kemampuan Penalaran Matematis Siswa Kelas IV Pada Materi Keliling dan Luas Bangun Datar di MI Ma’arif Polorejo - Uswatun Khazanah; Hestu Wilujeng (Indonesian Mathematics Education Journal, 2024)
Mathematics is one of the subjects that must be studied by students at school. One of the objectives of teaching mathematics is to train and develop students' mathematical reasoning abilities. In class IV at MI Ma'atif Polorejo there were several problems during the learning process for mathematics, including the teacher still using the lecture method in delivering learning, the teacher never using learning media in delivering mathematics material, the students were less enthusiastic when delivering the material. , students find it difficult to accept learning materials, some students are less interested in learning mathematics, students' ability to solve mathematical problems is still low, students' mathematical reasoning abilities are still low and grade IV learning outcomes in mathematics subjects are still low, namely there are 10 students out of 29 grade IV A students or the equivalent of 34.5% of students whose average evaluation results are still below the KKM, which is 70. Improving students' mathematical reasoning abilities must be accompanied by an appropriate learning process, so that learning objectives can be achieved. So, the learning carried out by the teacher has a very important influence on students' understanding of learning materials and students' mathematical reasoning abilities. The use of youtube video media in the mathematics learning process, with the hope that students' enthusiasm and motivation to learn, students' understanding of the material and students' mathematical reasoning abilities can increase. This study aims to analyze the effect of using Youtube video media on the mathematical reasoning abilities of fourth grade students on the circumference and area of ​​flat shapes at MI Ma'arif Polorejo. To answer the questions above, this study was designed with a quasi-experimental research design and used a pre-test – post-test control group design to collect data and was carried out at MI Ma'arif Polorejo. This study was conducted using a sample of 2 classes, namely class IV A and IV B. The sample selection in this study was conducted randomly based on the results of the pre-test. This study uses a test as an instrument in data collection. The data analysis technique used in this study was the t-test. The results of the calculation of the t-test obtained tcount = 4.63 while ttable = 1.6741 it can be concluded that tcount > ttable that is 4.63 > 1.6741. Thus, it can be concluded that H0 is rejected and Ha is accepted, which means that there are differences in the mathematical reasoning abilities of students whose learning uses Youtube video media with the mathematical reasoning abilities of students whose learning does not use Youtube video media in class IV at MI Ma'arif Polorejo. Thus, the use of Youtube video media affects the mathematical reasoning abilities of fourth grade students on the circumference and area of ​​flat shapes at MI Ma'arif Polorejo.